Molecular and morphological characterization of Glossina sp. and identification of associated Trypanosoma sp. in Nigeria including analysis for sialidase activity - Weber, Judith Sophie; Shaida, Stephen Saikiu; Ngomtcho, Sen Claudine Henriette; Musa, Usman Baba; Adamu, Ahmadu; Gbem, Thaddeus Terlumun; Berger, Petra; Mamman, Mohammed; Nok, Jonathan Andrew; Kelm, Sørge (PANGAEA, 2020)
These data sets include morphological and molecular data generated from a tsetse (Glossina sp.) collection carried out in Nigeria between 2014 and 2016. Traps were employed for one to three days in four different National Parks (Kainji Lake National Park, Old Oyo National Park, Cross River National Park, Gashaka Gumti National Park), one Game Reserve (Yankari Game Reserve) and two tsetse invested areas (Ijah Gwari, Tuongo). Each tsetse was identified morphologically and dissected in the field, all tissues preserved and used for further analysis. Selected tsetse wings were mounted and photographed to be used for morphometric analysis. The whole gut of each tsetse was homogenized in the field and partially preserved for DNA analysis and used to investigate for sialidase activity with a fluorescent substrate and a natural substrate. Analysis for sialidase activity was done by fluorescent measurement and reverse phase HPLC of processed gut samples. DNA was purified from preserved homogenized gut and used for phylogenetic analysis of tsetse by amplification of Cytochrome Oxidase C SU1 and Internal Transcribed Spacer-1 (ITS1). Presence of trypanosomes was investigated in gut and crudely extracted DNA from proboscis by amplification of ITS1. Identification of the respective trypanosome species was done based on lengths polymorphism of the ITS1 region as well as sequencing of selected ITS1 amplicons and additional glycosomal Glyceraldehyde-3-phosohate dehydrogenase.